Locoregional control, progression‐free survival and morbidity rates in N3 head and neck cancer patients with low primary tumour burden: A 301‐patient study. (16th September 2020) - Carsuzaa, Florent; Dufour, Xavier; Gorphe, Philippe; Righini, Christian; Cosmidis, Alain; Rogé, Maximilien; De Mones, Erwan; Servagi Vernat, Stéphanie; Tonnerre, Denis; Morinière, Sylvain; Dugas, Amaury; Malard, Olivier; et al.
Abstract: Objectives: In patients with N3 head and neck squamous cell carcinoma (HNSCC), N3 disease is associated with high regional relapse and metastatic risks. Patients with resectable N3 disease have better prognosis although their metastatic risk may be similar as in patients with unresectable disease. Neoadjuvant chemotherapy has been associated with lower metastatic rates, but N3 patients may die of rapid locoregional progression. We assessed outcomes with the three modalities in patients with low primary burden to better assess the specific prognosis of N3 disease. Methods: This retrospective multicentric study included T0‐2 N3 HNSCC patients. Outcomes and morbidity in upfront neck dissection (uND) vs non‐surgical groups were analysed and oncological outcomes and morbidity compared between patients undergoing chemoradiation or neoadjuvant chemotherapy in patients with initially unresectable N3 nodes. Results: Of 301 patients, 142 (47%) underwent uND, 68 (23%) neoadjuvant chemotherapy and 91 (30%) chemoradiation. The 24‐ and 60‐month incidence of locoregional relapse was 23.2% [18.3%; 28.4%] and 27.4% [21.8%; 33.3%]; it was lower in patients undergoing uND ( P  = .006). In patients with non‐surgical treatments, success rates were 57.8% [49.4%; 66.3%] after chemoradiation and 38.1% [29.6%; 46.7%] after neoadjuvant chemotherapy ( P  = .001). Overall morbidity was more frequent in patients undergoing uND (68.8%) ( P  < .001). Conclusion: uND improved locoregional control but increased morbidity and showed no survival benefit. Success rates were better after chemoradiation versus neoadjuvant chemotherapy. Neoadjuvant chemotherapy did not reduce metastatic rates but non‐responders to chemoradiation had poor PFS and survival rate, suggesting that predictive criteria are warranted.